Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jped.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of passive smoking on learning in elementary school

Abstract: The study demonstrated an association between passive exposure to tobacco smoke and learning difficulties at school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…1 Previous studies have reported that prenatal smoking exposure, premature birth, and asphyxia are linked to an increased risk of ADHD. 17,20 Likewise, our findings suggest that prenatal smoking exposure and premature birth increase ADHD comorbidity in children with SLD. EEG abnormality is present in 6.1 to 53.1% of children with ADHD.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…1 Previous studies have reported that prenatal smoking exposure, premature birth, and asphyxia are linked to an increased risk of ADHD. 17,20 Likewise, our findings suggest that prenatal smoking exposure and premature birth increase ADHD comorbidity in children with SLD. EEG abnormality is present in 6.1 to 53.1% of children with ADHD.…”
Section: Discussionsupporting
confidence: 57%
“…14 Previous studies have suggested that premature birth, expressive language delay, and prenatal smoking exposure increase the risk of SLD. 1,[15][16][17][18] Children with a developmental history of expressive language delay are more likely to suffer from poor academic performance and various learning disorders. 19 These manifestations are more significant when dyslexia and dysgraphia are present.…”
Section: Discussionmentioning
confidence: 99%
“…Although we adjusted for some potentially confounding factors which are known to be associated with infant development such as maternal socioeconomic status,21 maternal education,22 low birth weight,23 maternal exposure to passive smoking24 and maternal obesity,25 we were unable to adjust for those on which we had no data, such as maternal nutrition,26 depressive illness,27 stress and anxiety28 and alcohol consumption29 which could also potentially influence infant development but which were not measured in the SNAP trial. There remains therefore, the potential for residual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking during pregnancy may be the single most important avoidable cause of adverse pregnancy outcomes including increased infant mortality rates and the development of IUGR and PE [ 10 , 11 , 12 , 13 ]. More recently, passive secondhand smoke (SHS) exposure has been associated with adverse pregnancy consequences, including the development of IUGR, increased risk of newborn orofacial clefting, elevated risks of wheeze development in newborns, and even learning difficulties [ 14 , 15 , 16 , 17 ]. In addition, IUGR babies are linked to long-term sequelae of diseases, including adult hypertension, pulmonary complications, heart disease, stroke, and diabetes [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, passive secondhand smoke (SHS) exposure has been associated with adverse pregnancy consequences, including the development of IUGR, increased risk of newborn orofacial clefting, elevated risks of wheeze development in newborns, and even learning difficulties [14][15][16][17]. In addition, IUGR babies are linked to long-term sequelae of diseases, including adult hypertension, pulmonary complications, heart disease, stroke, and diabetes [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%